Cel uświęca środki? O współczesnym wymiarze politycznego makiawelizmu na przykładzie wyborów samorządowych w 2010 roku w województwie opolskim - Kaczmarek, Mirela (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The paper is an attempt to analyze the marketing activities of selected candidates running for office in the local authorities of the Opolskie Region in 2010. A large proportion of these candidates implemented the Machiavellian principle that the end justifies the means, and they tried to win power, almost trampling over corpses, using all available methods to succeed. Niccolò Machiavelli, the author of The Prince, argued five centuries earlier that the good of state justifies ruses, cruelty and violence. The present face of political Machiavellianism is different, as many people value power itself rather than the good of the state or region. As a result, voters observe a political farce under the official name of an election campaign. The local government campaign in the Opolskie Region in 2010 reminded a political circus with a number of pseudo-events keenly reported by the media, instead of real content that could give potential voters an idea of what the candidates had to offer. Some tried to win voters feeding them with sweets, others cleared snow from pavements in the middle of winter, yet others paid those who promised to vote for them. The latter are probably still suffering from post-election hiccups, as they will have to explain this electoral corruption in court.